2018
DOI: 10.1021/acs.jmedchem.7b01869
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing a Library of Human Cathepsin L Ligands: Identification of Macrocyclic Lactams as Potent Rhodesain andTrypanosoma bruceiInhibitors

Abstract: Rhodesain (RD) is a parasitic, human cathepsin L (hCatL) like cysteine protease produced by Trypanosoma brucei ( T. b.) species and a potential drug target for the treatment of human African trypanosomiasis (HAT). A library of hCatL inhibitors was screened, and macrocyclic lactams were identified as potent RD inhibitors ( K < 10 nM), preventing the cell-growth of Trypanosoma brucei rhodesiense (IC < 400 nM). SARs addressing the S2 and S3 pockets of RD were established. Three cocrystal structures with RD reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 79 publications
1
43
0
Order By: Relevance
“…For example, Shenoy et al showed that although Z-Phe-Tyr (O-tert-Butyl)-DMK binds to the same subsites of cathepsin L as observed for the Z-Phe-Tyr (O-tert-Butyl)-C(O)C(H)O ligand and finds some alternative interactions with residues from the active site pocket. This finding has been corroborated by other studies as well that suggest that structural features of ligands can influence the subsite composition of the cathepsin L enzyme [94,95,97,98]. Such information has been duly capitalized to develop different classes of inhibitors that are discussed next.…”
Section: Inhibitory Ligand Inhibition Constant (K I )supporting
confidence: 56%
See 1 more Smart Citation
“…For example, Shenoy et al showed that although Z-Phe-Tyr (O-tert-Butyl)-DMK binds to the same subsites of cathepsin L as observed for the Z-Phe-Tyr (O-tert-Butyl)-C(O)C(H)O ligand and finds some alternative interactions with residues from the active site pocket. This finding has been corroborated by other studies as well that suggest that structural features of ligands can influence the subsite composition of the cathepsin L enzyme [94,95,97,98]. Such information has been duly capitalized to develop different classes of inhibitors that are discussed next.…”
Section: Inhibitory Ligand Inhibition Constant (K I )supporting
confidence: 56%
“…Much excitement remains as new cathepsin L functions continue to emerge from specific cell types in the coming years. 4AXL X-ray 1.92 [190] 4AXM X-ray 2.80 [190] 5F02 X-ray 1.43 [191] 5I4H X-ray 1.42 [192] 5MAE X-ray 1.00 [145] 5MAJ X-ray 1.00 [145] 5MQY X-ray 1.13 [123] 6EZP X-ray 1.37 [98] 6EZX X-ray 2.34 [98] 6F06 X-ray 2.02 [98] Funding: S.K.P. gratefully acknowledges the financial support from the National Science Foundation (NSF); Grant no.…”
Section: Final Perspectivesmentioning
confidence: 99%
“…Insilico testing offers immediate insight into pathways and drugs that interact with these pathways to promote or inhibit their activity. Eleven studies have been published about previous drugrepositioning efforts for SARS-FCoVs [9][10][11][12][13][14][15][16][17][18][19]. These studies were identified using the keywords ("Drug Repurposing" OR "Drug Repositioning") AND (SARS OR MERS OR coronavirus OR COVID-19 OR SARS-CoV-2).…”
Section: Introductionmentioning
confidence: 99%
“…[54] For structure determination, the previously determined structure of mature rhodesain in complex with a macrolactam inhibitor (PDB: 6EX8) was used as a model for molecular replacement with PhaserMR of the phenix work suites after removal of the ligand and all water molecules. [24,[54][55][56] The prodomain was then built into the remaining electron density and final refinement was done with WinCoot. [57] MD simulations MD simulations were performed with the crystal structure of pro-rhodesain described in this manuscript but containing an active site cysteine residue instead of alanine.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…[18][19][20][21] The cleavage site is located in the linker between the pro-domain and the core protease domain. [22,23] While the rhodesain core protease domain has been crystallized in complex with different inhibitors including K11777 (PDB: 2P7U) [23][24][25][26] , a structure of the zymogen as an important intermediate of the parasitic protease maturation process is currently not available. In addition, the molecular details of the pH-dependent cleavage process remain unclear.…”
Section: Introductionmentioning
confidence: 99%